Perlindungan Hukum bagi Korban Penipuan dengan Dalih Investasi di Aplikasi Berbagi dan Cameto di Desa Weulun Kecamatan Wewiku Kabupaten Malaka - Joana Fransiska Manek; Thelma S.M. Kadja; Deddy R. CH. Manafe (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The purpose of this study is to analyze the legal protection for victims of fraud under the pretext of investment in the sharing and cameto applications in Weulun Village, Wewiku District, Malaka Regency. The type of research used by the author is Empirical Normative Legal research. The data sources in this research are primary and secondary data sources. The data collection techniques include; data collection through literature study and document study and primary data collection through interviews and questionnaires (questionnaires) given to sources. Analysis of data and legal materials in this study, namely using qualitative analysis in accordance with primary data and secondary data that has been obtained from the research results. Based on the results of the research, in general, victims of fraudulent investment have the right to obtain legal protection as stipulated in Law Number 21 of 2011 concerning OJK. The Investment Alert Task Force, OJK is authorized to: provide Preventive and Repressive Legal Protection. Perpetrators of criminal acts of fraud under the pretext of investment can be charged with the provisions of Article 378 of the Criminal Code Jo Article 28 paragraph (1) of the ITE Law. However, in this case the victim of the fraudulent investment fraud did not report it to the authorities. This is what causes the obstruction of the legal protection process for victims of fraudulent investment fraud. The factors that cause victims of fraud on the pretext of investment in sharing and cameto applications do not report to the police, among others; lack of understanding and knowledge (lack of information) of the community, lack of public trust, internal factors from the victims themselves.